Cell-specific expression of a Clara cell secretory protein-human growth hormone gene in the bronchiolar epithelium of transgenic mice. - Hackett, B P (1992)
Clara cell secretory protein (CCSP) is an abundant 10-kDa protein synthesized and secreted by nonciliated epithelial cells lining the respiratory and terminal bronchioles of the lung. CCSP gene expression is an informative developmental marker within the bronchiolar epithelium recapitulating cellular differentiation in the distal respiratory epithelium during late fetal and early postnatal life. To define the mechanisms that establish and maintain gene expression within this epithelium, CCSP-human growth hormone chimeric gene constructs were created and used to generate transgenic mice. RNA blot analysis of organs from F1 transgenic offspring and normal littermates revealed that cis-acting elements within 2.25 kilobases of the 5' flanking region of the CCSP gene were sufficient to direct lung-specific expression of human growth hormone. In situ hybridization and immunohistochemistry of individual bronchioles revealed that human growth hormone expression in the respiratory epithelium of these mice was confined to Clara cells, consistent with observations of the endogenous CCSP gene. Unexpectedly, founder animals and F1 transgenic offspring exhibited an unusual phenotype of growth retardation and delayed hair appearance, suggesting a unique effect of human growth hormone on normal intrauterine development. CCSP-human growth hormone transgenic mice provide a model to dissect the developmental mechanisms regulating gene expression during pulmonary epithelial cell growth and differentiation. Definition of the cis-acting elements determining such cell-specific expression will be of value in strategies for the somatic gene therapy of human pulmonary disease.